Analysis of The Role of Multi Jasa Sejahtera (MJS) Financing at KSPPS Bina Syari’ah Ummah East Java in Improving The Community Economy - Afifah, Nur Fidiyatul; Umam, M. Shaiful; Fahim, Achmad (Yayasan Rahmat Islamiyah, 2025)
The aims of this research is to analyze the role of MJS financing in improving the community’s economy, identify the factors influencing the selection of MJS financing, and examining the solutions for handling non performing financing at KSPPS Bina Syari’ah Ummah East Java. Then research is a field study with a qualitative approach, in wich primary and secondary data collected through observation, interviews, and documentation, and are analyzed descriptively. The results of the study indicate that MJS financing has a positive role in improving the community’s economy, especially as business capital, chosen due to factors such as motivation, needs, promotion, convenience, service, and low profit sharing, while non-performing financing is resolved through online reminders, direct visits, restructuring, and collateral protection if necessary.